2020
DOI: 10.1155/2020/6457079
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Polyethylene Glycol versus Oral Sodium Phosphate for Bowel Preparation in Unsedated Colonoscopy

Abstract: Aim. To identify the most effective laxative for bowel preparation in unsedated colonoscopy. Methods. Between April 2019 and April 2020, a total of 586 outpatients scheduled for unsedated colonoscopy at the First Hospital of Jilin University (Changchun, China) were randomized into one of two groups, namely, the polyethylene glycol (PEG) group or the oral sodium phosphate solution (OSP) group. The cleaning efficiency and other relevant clinical parameters were compared between the two groups. Results. Each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…( 16) Dong et al (2020) showed no significant difference in Polyethylene glycol and sodium phosphate solution preparations. (17) The present study observed that the male ratio for colonoscopy was higher than the females. Similar results were observed in the previous study.…”
Section: Discussionsupporting
confidence: 41%
“…( 16) Dong et al (2020) showed no significant difference in Polyethylene glycol and sodium phosphate solution preparations. (17) The present study observed that the male ratio for colonoscopy was higher than the females. Similar results were observed in the previous study.…”
Section: Discussionsupporting
confidence: 41%
“…Reviewing the literature, one concludes that polyethylene glycol (PEG) is the most extensively studied synthetic polymer for hydrogel development and application ( Figure S1B ). The hydrophilic polyether, with a repeat unit of –CH 2 CH 2 O–, has low toxicity and numerous biomedical applications [ 5 , 6 , 25 , 26 , 27 , 28 , 29 ]. Insoluble hydrogel networks can be generated by crosslinking PEG end-capped with acrylate groups (PEG-diacrylate (PEGDA)).…”
Section: Introductionmentioning
confidence: 99%
“…patients in the OSP group. 15 In this study, we observed that the largest number of colonoscopies was performed at the age of 40-60, and most of them were male. It can be concluded from previous studies that men have the highest detection rate of adenoma compared with women of the same age group.…”
Section: Discussionmentioning
confidence: 72%